ANALISIS KEBIJAKAN PENGELOLAAN TEMPAT PEMBUANGAN SEMENTARA (TPS) SAMPAH PROGRAM PENYEHATAN LINGKUNGAN PEMUKIMAN KEMENTERIAN PEKERJAAN UMUM DAN PERUMAHAN RAKYAT DI KOTA PEKANBARU - Ernawati Ernawati; Syapsan Syapsan; Hendro Ekwarso (Program Studi Pendidikan Ekonomi Universitas Riau, 2021)
The purpose of this study is to analyze the utilization and management of temporary storage places (TPS) for waste and to determine the factors that cause the number of temporary disposal sites (TPS) for environmental sanitation programs for the ministry of public works and public housing in the city of Pekanbaru. The data used are the results of interviews with the Head of the Pekanbaru City Environment and Sanitation Service and the Ministry of Public Works for the Work Unit for the Development of Environmental Health for Settlements (PLPP), the people of Pekanbaru City and community leaders, as well as the results of analysis of documents and records. The analysis was carried out by descriptive method, using a qualitative approach to this type of phenomenological research. The results of the analysis show that the management and utilization of temporary waste disposal sites (TPS) can fulfill what the community needs with encouragement and sustainability in TPS management, and socialization is needed about the 3R TPS so that the people of Pekanbaru City can participate in running the program. And the factors causing the management and utilization of temporary waste disposal sites (TPS) in Pekanbaru City such as communication factors, resource support, attitudes and dispositions of officials, bureaucratic structures and community support are not functioning properly.